Music's context-dependent influence on oxytocin, social bonding, and emotion regulation: a systematic review - Chu, Ting-Hsuan; Tsai, Chen-Gia (Frontiers in Cognition, 2026)
ObjectiveThis systematic review aims to explore how individual and group musical activities influence social bonding and emotion regulation through the oxytocinergic system.MethodsFollowing the PRISMA 2020 guidelines, a systematic search of PubMed, Embase, Scopus, Web of Science Core Collection, and PsycInfo was conducted to identify studies up to October 2024, supplemented by a manual search. One reviewer screened studies, extracted data, and assessed the study quality. Framework synthesis and narrative synthesis were conducted to integrate findings.ResultsA total of 1,865 records were identified. After reviewing the full-text papers, 20 studies (seven randomized controlled trials and 13 quasi-experiments) were included, which involved 877 participants across healthy and clinical populations. The reviewed interventions included singing, playing instruments, listening to music, and music therapy. Most studies reported improvements in psychosocial outcomes, such as reduced anxiety and depression or enhanced social cognition, but they do not always align with peripheral oxytocin (OXT) changes. However, certain psychosocial outcomes or contexts revealed relatively consistent patterns in OXT responses, suggesting the presence of context-dependent modulation. Short-term interventions often reported detectable peripheral OXT changes, which only partially reflected the temporary activity of magnocellular OXT neurons in the hypothalamus. No significant changes in baseline peripheral OXT levels were observed after long-term interventions.ConclusionMusic-induced OXT responses are context-dependent. The bidirectional modulation of OXT supports social bonding and emotion regulation in musical contexts. Clinicians and music therapists should carefully consider therapeutic goals, individual differences, and environmental factors when designing music therapy.